Pengaruh Promosi Dan E-WOM Terhadap Minat Beli Produk Pakaian Syar’i Pada E-Commerce Shopee (Studi Kasus : Mahasiswa Universitas Islam Negeri Sumatera Utara) - Fitria Intan Sri Dewi; Tri Inda Fadhila Rahma; Rahmi Syahriza (Jurnal Manajemen Akuntansi (JUMSI), 2023)
The pattern of public consumption demand for clothing makes Indonesia's fashion trend more diverse and affects the consumption pattern of fashion Syar'i students. Buying and selling online is a trend that has now permeated the world of schools and colleges. The development of internet technology has brought changes in behavior that can be seen from the shopping habits of people who switch to online shopping. Shopee is an online shopping site with a large number of visitors. With the increasing exposure of Shopee promotions, especially the monthly twin date Big Promotion, online purchases are getting higher. Positive and negative opinions and reviews of online shopping sites through Electronic Word of Mouth (E-WOM) on buying interest with increased promotional activities and consumer confidence in the online purchasing process became the basis of this study. This study aims to determine the effect of promotion and E-WOM on interest in buying Syar'i clothing products on Shopee E-Commerce (case study of students of the state Islamic University of North Sumatra). This study is a type of quantitative research using Non Probability Sampling sampling method with Purposive Sampling technique. The population used in this study were students of the state Islamic University of North Sumatra with a sample of 100 respondents. The Data in this study are primary data using questionnaires that are distributed online to 100 respondents. Data analysis techniques used multiple linear regression. The results of the hypothesis testing showed that the promotion and e-WOM simultaneously significant effect on interest in buying clothing products Syar'i on e-Commerce Shopee (case study of students of the state Islamic University of North Sumatra).